Rituximab vs Low-Dose Mycophenolate Mofetil in Recurrence of Steroid-Dependent Nephrotic Syndrome in Children and Young Adults: A Randomized Clinical Trial - Ravani, Pietro (JAMA Pediatr, 2021)
This randomized clinical trial examines the superiority of a single dose of rituximab vs low-dose mycophenolate mofetil in preventing the recurrence of steroid-dependent nephrotic syndrome in children and young adults.